Analisis Struktur Nafkah Anggota Pengelola Hutan Adat Titian Teras di Desa Demang Kabupaten Sarolangun - Marwoto, Marwoto; Ulfa, Maria; Islahunnufus, Tamara (Universitas Batangahari Jambi, 2025)
The social forestry program was first mandated in Forestry Law Number 41 of 1999 which states that the main objective of community forest management is for equitable and suistainable community walfare. The social forestry program in Demang Village, using the customary forest scheme, has become one of the means or livelihood strategies for the community and has garnered high levels of participation in social forestry. This will affect the livelihood structure based on the livelihood sources of Titian Terrace customary forest management members. The aim of this research is to analyze the livelihood structure of village community of the Titian Teras traditional forest management and analyze the contribution of the Titian Teras traditional forest to the manager's income. The data analysis used in this research is quantitative analysis and descriptive analysis by calculating revenue, cost , income and contribution on the income of customary forest-managing communities. The results of the research show that the livelihood structure of Titian Terrace customary forest management members in Demang Village is related to total on-farm income of IDR. 397,770,950/year, off farm income Rp. 131,948,700/year, and non-farm income Rp. 1,636,674,000/year. With the total income of the household income structure being Rp. 2,166,393,650/year with an average of Rp. 180,601,129/Year. Meanwhile, the total income in customary forest areas is Rp. 8,310,400/year with an average of Rp. 692,533/Year. Meanwhile, the contribution of customary forests to the total household income of members of customary forest management is 0.3821%.